Development and evaluation of artificial expandable pillars for hard rock mining. (October 2018) - Li, Yuanhui; Li, Kunmeng; Feng, Xiating; Cai, Ming
Abstract: In this paper, a new artificial expandable pillar, which uses a chemical mixture that expands when water is introduced, is developed for roof support in hard rock mining. Firstly, the active support stresses and load bearing properties of an expandable device were measured in laboratory. The test results show that the initial active support stresses are generated at a rapid rate and then remain constant. The support stress can be increased by decreasing the reserved gap between the roof and the top of the expandable device in the case of a fixed amount of the expandable material. Meanwhile, the bearing capacity of expandable devices increases with loading. Secondly, based on the laboratory test results, the support mechanism of the expandable pillar is analyzed. Thirdly, to verify the effectiveness of the expandable pillar in-situ, a field test was carried out in a large room and pillar mining stope at an underground mine in China. An expandable pillar only takes 4–5 h to set up and generate the pre-stress, which is much shorter than the construction time required for traditional artificial pillars. Pressure gauges were installed to monitor the support pressures of expandable pillars in the process of recovering some of the natural pillars. The test results demonstrate that the initial active support stresses of the expandable pillars are maintained approximately at 11 MPa, which are much higher than the pressures that can be provided by mechanically pre-stressed artificial pillars which is about 0.5 MPa. During the recovery of the residual natural pillars, the expandable pillars show strain-hardening bearing behaviors. Lastly, the economic benefits, the weak parts, and the ultimate bearing capacity of the expandable pillar are analyzed and results are presented. Generally speaking, replacement of natural pillars with artificial ones can increase the ore recovery rate to 100%, and the cost of expandable pillars is cheaper approximately 47% that of traditional equivalent shotcrete pillars. Additionally, numerical modeling results show that weak areas of the overall structure of an expandable pillar are the contact points of support posts and steel plates at both ends, based on the configuration of the field tested pillars, the ultimate bearing capacity of the tested expandable pillar is estimated to be can reach about 4651 kN. Comparing with traditional artificial supports, the expandable pillars provide higher initial support stresses to stope roofs and they continue to carry loads in a strain-hardening manner. As a result, the expandable pillars can stabilize an excavation with small roof deformation. Successful application of the expandable pillars can enable mines to improve their recovery rates of natural resources in a safe working environment with favorable financial benefits.